Junior Students’ Self-Regulation Strategies in Dealing with Assignments - Laurentius Krisna Septa Bernanda (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
One of the courses in English Language Education Study Program of Sanata Dharma University is Play Performance Course. In this course, students work in groups. Students needs to plan, monitor, and evaluate their works. Those activities are considered as self-regulated activities. This research provides an issue to discuss: To what extent do the junior students use self-regulation strategies in dealing with assignments? This study intends to describe self-regulation strategies used by the junior students of the study program. The researcher used in depth-interview as the medium of data gathering. The participants of the research were the students of English Language Education Study Program of Sanata Dharma University who had taken Play Performance Class in the third year. They came from batch 2015. The result shows that they use four, instead of five, self-regulation strategies. Independence learning as the characteristic of activities played important role in divining such activities in order to enhance their cognitive and other aspects. This research might help the students of English Language Education Study Program to modify their strategies in learning, especially in dealing with their assignments.